2016
DOI: 10.1038/leu.2016.244
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a constrained azacyclic FTY720 analog enhances anti-leukemic activity without inducing S1P receptor activation

Abstract: The frequency of poor outcomes in relapsed leukemia patients underscores the need for novel therapeutic approaches. The FDA-approved immunosuppressant FTY720 limits leukemia progression by activating protein phosphatase 2A and restricting nutrient access. Unfortunately, FTY720 cannot be re-purposed for use in cancer patients due to on-target toxicity associated with S1P receptor activation at the elevated, anti-neoplastic dose. Here we show that the constrained azacyclic FTY720 analog SH-RF-177 lacks S1P recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(99 reference statements)
3
19
0
Order By: Relevance
“…However, FTY720 functions primarily through immunosuppression by internalizing and activating the sphingosine 1 phosphate receptor (S1PR) [136]. FTY720 analogs, such as SH-RF-177, induce cell death in part through PP2A activation without the activation of S1PR, increasing the clinical significance of these compounds [137].…”
Section: Indirect Protein Phosphatase 2a (Pp2a) Activationmentioning
confidence: 99%
“…However, FTY720 functions primarily through immunosuppression by internalizing and activating the sphingosine 1 phosphate receptor (S1PR) [136]. FTY720 analogs, such as SH-RF-177, induce cell death in part through PP2A activation without the activation of S1PR, increasing the clinical significance of these compounds [137].…”
Section: Indirect Protein Phosphatase 2a (Pp2a) Activationmentioning
confidence: 99%
“…FTY720 acts directly on lymphocytes, and exerts immunosuppressive effects. [8][9][10][11][12] Therefore, FTY720 was once widely recognized in the field of transplantation immune tolerance. Whether FTY720, which plays a key role in the migration, differentiation and homing of lymphocytes, can fully regulate the maternal immune system and the local immunity of the maternal-fetal interface by creating the microenvironment for pregnancy immune tolerance?…”
Section: Discussionmentioning
confidence: 99%
“…Thus S1P signaling may directly impact the GvL effect by regulating leukemia cells sensitivity to apoptosis. Various studies have shown that FTY720 has direct effects on certain leukemia growth and survival though this has been shown not to be due to S1P signaling by using FTY720 analogues that lack S1PR activity [ 65 ]. However, a recent study has shown that S1PR1 signaling enhances cell survival in naïve T cells via the modulation and mitochondrial function and metabolism.…”
Section: The Effect Of Sipr Signaling On the Graft Vs Leukemia Efmentioning
confidence: 99%